Nested ecologies of childhood: A microbial turn in developmental theory - Millei, Zsuzsa; Lee, Nick; Alminde, Sarah; Breinholt, Asta; Grönroos, Mira; Hohti, Riikka; Keto, Sami; Roslund, Marja; Spyrou, Spyros; Tammi, Tuure; Warming, Hanne; Madureira Ferreira, Juliene (Mehmet Toran, 2026)
This article expands Bronfenbrenner’s bioecological model by integrating biological and ecological processes—particularly microbial life—into its core concept of proximal processes. Drawing on host–microbiome research and the concept of the child-as-ecosystem, we reconceptualize the developing person as a multispecies being embedded within nested ecological systems. Through four interdisciplinary encounters—spanning social stratification, family separation, socialisation, and environmental health—we demonstrate how microbial diversity and ecological entanglements shape children’s development, well-being, and learning. We argue that BEM’s human-centered framework must evolve to reflect multispecies interdependencies and ecological realities, especially in the context of biodiversity loss and climate change. This rethinking has direct implications for early childhood education, research, and policy, offering a more ecologically attuned model of development.
Keywords: biodiversity; childhood; Brofenbrenner; ecosystem; microbiome; child development